2019
DOI: 10.1111/ggi.13628
|View full text |Cite
|
Sign up to set email alerts
|

Association between delirium, adverse clinical events and functional outcomes in older patients admitted to rehabilitation settings after a hip fracture: A multicenter retrospective cohort study

Abstract: Aim The aim of the present study is to investigate how delirium and adverse clinical events (ACE) contribute independently and in combination to functional outcomes in older patients admitted to rehabilitation settings after a hip fracture. Methods This is a multicenter retrospective cohort study of patients aged ≥65 years admitted after hip fracture surgical repair to three Italian rehabilitation units. Delirium on admission was evaluated with the Confusion Assessment Method. ACE during the rehabilitation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…The presence of dysphagia and especially the acute dysphagia related for instance to the presence of delirium can lead to malnutrition with adverse outcomes on the rehabilitation process. In our investigation we found a 19% prevalence of malnutrition, which is likely underestimated compared to previous reports which indicate a prevalence ranging from 19 to to 46% assessing the nutritional status with the Mini Nutritional Assessment [28][29][30]. In our study protein supplements were prescribed only in 22.7% of the patients.…”
Section: Discussioncontrasting
confidence: 75%
“…The presence of dysphagia and especially the acute dysphagia related for instance to the presence of delirium can lead to malnutrition with adverse outcomes on the rehabilitation process. In our investigation we found a 19% prevalence of malnutrition, which is likely underestimated compared to previous reports which indicate a prevalence ranging from 19 to to 46% assessing the nutritional status with the Mini Nutritional Assessment [28][29][30]. In our study protein supplements were prescribed only in 22.7% of the patients.…”
Section: Discussioncontrasting
confidence: 75%
“…Return to independence in activities of daily living (ADLs) was less likely for those >85 years old (20% vs. 44%), with dementia (8% vs. 39%) and with a Charlson comorbidity index greater than 2 (23% vs 44%) [52] Functional outcomes after a hip fragility fracture seem to depend more on patient characteristics than treatment-related factors [127] In a retrospective cohort study of 519 patients with hip fracture admitted to rehabilitation settings, it has been reported that both delirium and clinical adverse events (infections, respiratory failure, pulmonary embolism, falls) affected functional outcome. A clinical orthogeriatric approach is necessary in order to minimize the impact of these adverse events on the rehabilitation program [128].…”
Section: Functional Recoverymentioning
confidence: 99%
“…The emphasis is on primary prevention using multicomponent, non-pharmacological interventions targeted to high-risk patients. 11,12 Various screening instruments, such as the Confusion Assessment Method (CAM), 4As Test (4AT), Delirium Triage Screen (DTS), Delirium Rating Scale (DRS) and Nursing Delirium Screening Checklist (NuDESC), have been developed to identify high-risk patients as well as diagnose and rate the severity of delirium. 13 Once delirium is detected, a comprehensive assessment is required and management strategies implemented.…”
Section: Improving the Quality Of Delirium Practices In A Large Australian Tertiary Hospital: An Evidence Implementation Initiative Reseamentioning
confidence: 99%
“…Typically, the management of delirium involves a multicomponent approach that includes reorientation, adequate hydration and nutrition, sleep promotion, early mobilisation, reduction of psychoactive drugs and optimising use of vision and hearing devices. 12 It also requires an interdisciplinary approach that includes doctors, nurses and rehabilitation therapists along with well-informed and engaged families or caregivers. Families or caregivers, when provided with adequate information about the nature of delirium, symptoms and their integral role in the prevention Discussion: The quality improvement activity highlighted that education remains one of the most important and critical first steps in facilitating change in clinical practice.…”
Section: Improving the Quality Of Delirium Practices In A Large Australian Tertiary Hospital: An Evidence Implementation Initiative Reseamentioning
confidence: 99%